2006
DOI: 10.1002/ajh.20699
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma followed by paroxysmal nocturnal hemoglobinuria: A unique clinical association in the context of multiorgan autoimmunity with a potential role for CD8+ T lymphocytes

Abstract: Seven years after a surgically resected thymoma, a female patient affected by myasthenia gravis and Good's syndrome presented with paroxysmal nocturnal hemoglobinuria (PNH). Co-culture experiments and spectratyping analyses indicated that CD8+ lymphocytes were involved in damaging hematopoietic precursors. While PNH clones have been identified in various hematological disorders, the sequential association of thymoma and PNH has been unreported so far. Am. J. Hematol. 81:774-778, 2006. V V C 2006 Wiley-Liss, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The most common disorders affecting bone marrow precursors are pure red cell aplasia (PRCA) and ‘pure B cell aplasia’ (Good’s syndrome: thymoma and hypogammaglobulinaemia) (3–4% of patients). A few patients have also been described with agranulocytosis, myelodysplasia or paroxysmal nocturnal haemoglobinuria . The pathogenesis of these complications is thought to involve either the production of autoantibodies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most common disorders affecting bone marrow precursors are pure red cell aplasia (PRCA) and ‘pure B cell aplasia’ (Good’s syndrome: thymoma and hypogammaglobulinaemia) (3–4% of patients). A few patients have also been described with agranulocytosis, myelodysplasia or paroxysmal nocturnal haemoglobinuria . The pathogenesis of these complications is thought to involve either the production of autoantibodies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Palmieri et al reported on the occurrence of paroxysmal nocturnal haemoglobinuria in a thymoma patient seven years after thymectomy. Causatively, they were able to attribute the reduction of circulating erythroid and myeloid progenitors to altered CD8+ T cells in this patient (126).…”
Section: Paroxysmal Nocturnal Haemoglobinuriamentioning
confidence: 73%
“…One proposed pathogenesis in MDS is autoantibodies that directly reject against hematopoietic cells, which was supported by the similar immune dysregulation of CD4 and CD8 T cells found in Good's syndrome [11,12]. In addition, CD8 T cells are proved to be involved in damaging hematopoietic precursors [6]. In the National Comprehensive Cancer Network guidelines of MDS, immunosuppressive treatments are reasonable choices in patients with MDS and hypocellular bone marrow, HLA‐DR15, and positive clones of PNH or young individuals at low‐ to intermediate‐risk.…”
Section: Discussionmentioning
confidence: 89%
“…Due to the dysfunction of both B and T lymphocytes, patients with Good's syndrome are more vulnerable to various pathogens, such as encapsulated bacteria, virus, fungus, and opportunistic infections. In addition to myasthenia gravis and Good's syndrome, paraneoplastic syndromes associated with thymoma (parathymic syndromes) could also present with autoimmune‐mediated hematological disorders, such as pure red cell aplasia, aplastic anemia, agranulocytosis, hemolytic anemia, pernicious anemia, and paroxysmal nocturnal hemoglobinuria [1–6]. Furthermore, myelodysplastic syndrome (MDS) is a heterogeneous group of clonal hematopoietic stem cell diseases characterized by cytopenia(s), dysplasia in one or more lineages, and ineffective hematopoiesis, and is associated with a variable risk of transformation to acute leukemia.…”
Section: Introductionmentioning
confidence: 99%